Endophytes. Volume 1 : biology and biotechnology - Maheshwari, D. K. (Springer, 2017)
This book discusses the latest developments in our understanding of microbial endophytes, their ecology, diversity and potential biotechnological applications. It covers all the latest advances concerning the endophytic interaction of microorganisms in a wide array of plants, reported on by experts from the entire globe. The diverse microbial community, which consists of archaeal, bacterial, fungal and protistic taxa, can be found in all plants. The endophytic lifecycle reveals how microorganisms play essential roles in plant growth, fitness and diversification. Diversity is an integral component of ecology. In soil ecology, below-ground interactions of plant and microorganisms are accomplished by endophytes, which reside in the plant's internal tissues. The microbial world in general and endophytes in particular reflect a unique degree of genetic and functional (metabolic) diversity. Currently, significant attention is being paid to endophytic microorganisms, as their repertoire of cells and metabolites hold immense potential with regard to biotechnological applications for sustainable development. The diversity of bacterial endophytes guarantees that there are endophytes capable of forming compatible associations with all agronomically important plants, including monocots and dicots. The study of endophytes' diverse nature in connection with biodiesel, medicinal and agriculturally important crop can lead to a better understanding of applicable facets. The topics in this dynamic field of study are so diverse and vast. This volume will benefit all botanists, microbiologists, ecologists, plant pathologists, physiologists, agronomists, molecular biologists, environmentalists, policymakers, conservationists and NGOs working to protect species and prevent the loss of biologically significant genetic material.
""5.3.4 Genes Involved in Plant Growth Promotion""
Keywords: Endophytes.; elektronické knihy; electronic books